Empowering Students’ Reading Comprehension Through Cornell Note-Taking Method - Rina Asrini Bakri; Hamid Ismail; Saiful Saiful; Hervina Syam (Celebes Scholar pg, 2022)
The purpose of this research was to determine whether or not using the Cornell note-taking method improves students' reading comprehension while they are enrolled in the first grade at MA-Al Hidayah. In this study, a pre-experimental research design was used, and participants in one group had a pre-test, treatment, and post-test. The overall sample size was thirty students, and the approach utilized was called purposive sampling. This study made use of a multiple-choice questionnaire as its tool. The findings of this study indicate that the pre-test mean score for students was 54.38, but that it increased to 79.06 after the intervention. It is possible to draw the conclusion that the students' reading comprehension increased, and this indicates that using the Cornel Note Taking approach led to an increase in the students' reading comprehension.